2010
DOI: 10.1111/j.1349-7006.2010.01737.x
|View full text |Cite
|
Sign up to set email alerts
|

Association of a novel long non‐coding RNA in 8q24 with prostate cancer susceptibility

Abstract: Recent genome-wide association studies reported strong and reproducible associations of multiple genetic variants in a large ''gene-desert'' region of chromosome 8q24 with susceptibility to prostate cancer (PC). However, the causative or functional variants of these 8q24 loci and their biological mechanisms associated with PC susceptibility remain unclear and should be investigated. Here, focusing on its most centromeric region (so-called Region 2: Chr8: 128.14-128.28 Mb) among the multiple PC loci on 8q24, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
209
1
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 267 publications
(220 citation statements)
references
References 35 publications
8
209
1
2
Order By: Relevance
“…Recent studies have indicated that lncRNAs are transcribed from cancer risk loci and that these transcripts can play important roles in tumorigenesis. [30][31][32] Here, we used RNA-seq to identify two estrogenregulated lncRNAs (CUPID1 and CUPID2) that might contribute to the risk of developing breast cancer by modulating pathway choice of DSB repair.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have indicated that lncRNAs are transcribed from cancer risk loci and that these transcripts can play important roles in tumorigenesis. [30][31][32] Here, we used RNA-seq to identify two estrogenregulated lncRNAs (CUPID1 and CUPID2) that might contribute to the risk of developing breast cancer by modulating pathway choice of DSB repair.…”
Section: Discussionmentioning
confidence: 99%
“…One of the overexpressed lncRNAs in prostate cancer, PCGEM1, is tissue specific and PCa-associated lncRNA gene (15), whereas another highly expressed lncRNA, PRNCR1 (PCAT8), is pervasively transcribed from the critical region of 8q24 Region 2, which is significantly associated with PCa susceptibility (17). Previous studies also demonstrated that a novel long non-coding RNA (named PlncRNA-1) was frequently overexpressed in PCa cell lines and tissues and associated with cell viability and cell apoptosis (18).…”
Section: Introductionmentioning
confidence: 99%
“…HULC, for example, is highly expressed in HCC and in colorectal carcinomas that metastasized to the liver, 96,105 but not in the primary colon tumors or in non-liver metastases, whereas other three lncRNAs, PCGEM1, DD3 and PRNCR1, have been associated solely with prostate cancer. 102,[106][107][108][109] Another tissue-specific lncRNA is papillary thyroid carcinoma susceptibility candidate 3 (PTCSC3), which is thyroid specific and downregulated in tumor tissue compared with unaffected thyroid tissue. 110 A key goal for future progress is to identify lncRNAs that could potentially serve as biomarkers for specific disease states.…”
Section: Discussionmentioning
confidence: 99%
“…101 A novel lncRNA termed 'PRNCR1' (prostate cancer non-coding RNA 1) is upregulated in some of the prostate cancer cells as well as precursor lesion prostatic intraepithelial neoplasia, knockdown of PRNCR1 can attenuate the viability of PC cells and the transactivation activity of the androgen receptor. 102 Although our understanding of the molecular mechanisms of lncRNA function is limited, some features of lncRNAs, including structural scaffolds for protein complexes and complex RNA structural motifs, make them ideal candidates for therapeutic intervention. 103 Preventing the interactions of HOTAIR with the PRC2 or LSD1 complexes, by targeting endogenous HOTAIR and/or using small molecular inhibitors of PRC2, for example, may limit the metastatic potential of breast cancer.…”
Section: Lncrnas As Diagnostic and Therapeutic Toolsmentioning
confidence: 99%